Mitomycin C instillation following ureterorenoscopic laser ablation of upper urinary tract carcinoma - Aboumarzouk, Omar M. (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Instillation of Mitomycin C (MMC) should prevent implantation of cancer cells released during endoscopic treatment and prevent recurrences as seen in carcinoma of the bladder. AIM: To develop and evaluate a protocol for a single dose MMC instillation following Holmium: YAG laser ablation of upper urinary tract transitional cell carcinoma (UUT-TCC). SETTING AND DESIGN: A single institute prospective study. MATERIALS AND METHODS: MMC instillations protocol was designed and offered to patients between August 2005 and April 2011. Following tumor ablation, MMC was instilled into upper urinary tract (UUT) over 40 minutes. All the patients were regularly followed up. RESULTS: Twenty UUT units (19 patients) were managed for UUT-TCCs using our MMC protocol. Two UUT units had G1pTa tumors, 14 had G2pTa, 2 had G3pTa, and 2 had G3pT1. At a mean follow-up of 24 months (range 1-72 months), 13/20 (65%) of the UUT units remained cancer-free, 3 (15%) UUT units developed stricture and were treated with endoscopic dilatation, only 1 (5%) of these developed long-term complications. None of the patients developed postoperative renal impairment or systemic side-effects. CONCLUSIONS: Using a set standard protocol, MMC can safely be instilled into the UUT after TCC ablation with minimal complications or side effects, good preservation of renal function, and with a low recurrences rate comparable to the literature.